Integrating Tawazun and Wasatiyyah: A Qualitative Literature Study on Work-Life Balance in Contemporary Muslim Contezts - Sirojuddin, Ahmad Sholihin (JURNAL PENELITIAN KEISLAMAN, 2025)
The contemporary Islamic era presents challenges for modern society in maintaining a balance between work and life needs. This article explores the concept of work -life balance in the application of tawazun and washatiyyah attitudes by highlighting how they manage the balance between professional, social, and religious obedience activities amidst changing times, using a qualitative literature study approach, this study examines various factors that influence life balance, including Islamic values, work culture, social pressure, By implementing the concept of work life balance in everyday life, the implications obtained are so many, starting from the psychological dimension. The results of the study show that society is able to face between fulfilling worldly expectations, such as education and career, and carrying out the needs of the afterlife that will come at any time according to Islamic teachings.